Beyond BMI: The Synergistic Effect of Ultra-Processed Food Consumption and Sedentary Behavior on Gut Microbiota and Systemic Inflammation in Young Adults with Early Metabolic Syndrome – A Longitudinal Cohort Study - Ian Astarina Mas'ud; Restu Auliani; Erba Kalto Manik; Yan Deivita; Yeni Aryani; Ani Laila (International Journal of Public Health Excellence (IJPHE), 2026)
Background: Body mass index (BMI) inadequately captures metabolic risks driven by modern lifestyles, particularly the combination of ultra-processed food (UPF) intake and sedentary behavior. While each factor independently fosters low-grade systemic inflammation, their synergistic impact on the gut microbiota–inflammation axis in young adults with early metabolic syndrome (MetS) remains unexplored. Objective: This longitudinal cohort study examined the independent and synergistic effects of UPF consumption and sedentary behavior on gut microbiota composition and systemic inflammatory biomarkers in Indonesian young adults with early MetS over 12 months. Methods: We recruited 400 participants aged 20–30 years meeting 1–2 ATP III criteria for MetS. Dietary intake was assessed with a validated semi-quantitative FFQ with NOVA classification; sedentary time was measured via triaxial accelerometers. Gut microbiota was profiled using 16S rRNA sequencing (V3–V4 region), and hs-CRP, IL-6, and TNF-α were quantified at baseline and 12 months. Participants were stratified into four groups by median splits of UPF energy share (%kcal) and daily sedentary time. Generalized estimating equations tested synergistic interactions on inflammation, and mediation analyses evaluated microbiota diversity pathways. Results: The high-UPF/high-sedentary group exhibited the greatest increases in hs-CRP (+1.78 mg/L), IL-6 (+2.95 pg/mL), and TNF-α (+3.12 pg/mL), with a significant multiplicative interaction (p<0.001). Shannon diversity declined most sharply in the high-UPF/high-sedentary group (−0.32), paralleled by a rise in the Firmicutes/Bacteroidetes ratio (+0.47). Mediation analysis showed that 31.4% of the synergistic effect on hs-CRP was mediated by loss of diversity. Conclusion: Co-occurring high UPF consumption and sedentary behavior synergistically amplify systemic inflammation partly through gut dysbiosis in early MetS, underscoring the need to target both dietary and physical activity domains beyond BMI-centric strategies